Prototipo de sistema de vigilancia de ganado usando red de supervisión inalámbrica para prevención de abigeato (2016)
This article shows the development of a prototype for the monitoring of livestock using a wireless supervision network with the goal of preventing cattle theft.  The monitoring system consists of two nodes:  the supervision node and the administrator node.  The supervisor unit sends a unique identification code to the administrator node via RF radio frequency communication at time intervals of 5 minutes.  The administrator node is composed of another RF receiver module, a digital processor and an SMS/GPRS (Send Message Short/General Packet Radio Service) communication module in order to send a text message to a cellphone and warn the user of possible theft.  The developed prototype was validated for an experimental range of 100m of distance between transmitters/receiver and for a limited number of 10 units.  The system is scalable in order to cover a greater number of livestock and at a greater surveillance distance, able to cover up to a distance of 1.4km.